Kolonialisme Inggris di Australia - Sari, Puspita; Nugroho, Alfan; Irwanto, Dedi; Pamulaan, Alif Bahtiar (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2024)
In this article we will discuss British Colonialism in Australia. Colonialism is a time when a country is controlled by another, stronger country. Most countries in the world have experienced the practice of colonialism by other nations, one of which is Australia. Using a qualitative descriptive method through a literature study approach. This research was conducted to practice knowing British colonialism in Australia. The results of this research show that British colonialism in Australia has had many impacts felt by Australia’s indigenous population, namely the Aborigines.